PREVALENCE OF HUMAN PAPILLOMA VIRUS IN CANCEROUS AND PRE-CANCEROUS ORAL LESIONS USING SALIVA, SERUM, AND PLASMA ASSAY - Nelly Nainggolan; Wahyu Hidayat (Dentino : Jurnal Kedokteran Gigi, 2021)
ABSTRACTIntroduction: As many as 90%-95% cases of oral cancer are oral squamous cell carcinoma. In South and Southeast Asia, the prevalence of oral cancer is high. Oral cancer is ranked sixth for the most frequent malignancies in Asia with nearly 274,300 new cases occurring every year. Head and Neck Squamous Cell Carcinoma is one of the main public health concerns with 1-2% incident of all cancers worldwide and is also the sixth most common malignant tumor. Human Papillomavirus (HPV) is a DNA virus which is also known as the cause of head and neck cancer. Among all malignancies, oral cancer is one of the conditions where salivary examination can be used to detect oral cancer because it contacts directly with the lesions. The relationship between human papilloma virus (HPV) and oral squamous cell carcinoma has been extensively studied and shows that HPV-16 & 18 can be detected in saliva, serum or plasma samples and patient biopsies. Purpose: This systematic review aims to reveal the presence of human papilloma virus in cancerous and pre-cancerous lesions of the oral cavity by examining saliva, serum or plasma. Methods: Systematic Review was carried out using the PRISMA method. Articles with clinical trial types sourced from electronic searches were obtained through the PubMed, Research Gate and Google Scholar portals using keywords: Human Papilloma Virus, Oral Cancer, and Saliva. Conclusion: Based on the results, it is concluded that HPV is detected in oral cavity cancers, oropharyngeal, oral squamous cell carcinoma and Oral Potentially Malignant Disorders.Keywords : Human Papilloma Virus, Oral cancer, Saliva